Evaluación de cicatrización en cortes de poda en Morus alba L. (Moraceae) en el área urbana de Mendoza (Argentina) - Elmida, Carina (2012)
The percentage of healing was assessed in pruning cuts of Morus alba L. (Moraceae) in urban environment. Approximately 400 trees, randomly chosen across the Great Mendoza area, were analyzed. A total of 800 records were considered. Cut diameter, percentage of healing, location of pruning cuts (trunk, primary and secondary branches) were taken into consideration. Callus formation (healing) was evaluated as percentage of the pruning area: < 30%, 30-60%, > 60% and100%. Results show that 75% of cuts smaller than 8 cm diameter heal between > 60% and 100%; between 10-13 cm, more than 50% of cuts shows a low percentage of healing (30-60% and < 30%); and as of a diameter of 14 cm, approximately 75% of cuts heal < 30%. Results allow concluding that, in managing this species in urban environment, it is convenient to do a maintenance pruning with small cuts that heal correctly and prevent access of plagues.